(untitled) (Journal of Global Accounting, 2025)
Audit communication tool – audit report has long been criticized for ineffectiveness in communicating audit findings to stakeholders. Following plethora of audit failures, a number of reforms were introduced to enhance the communication of key audit findings. This study identified the disclosure of key audit matters and audit engagement partners’ name as core reforms to the audit report and examined their effects on the quality of audit of listed non-financial firms in Nigeria. Data were extracted from the audited financial reports of one hundred and two listed non-financial firms across ten (10) industries. The findings, using fixed effect method to estimate the panel model, indicated that both reforms have positive and significant effects on earnings management thereby suggesting a reduction on audit quality in listed non-financial firms in Nigeria. The study submitted, amongst others, that key audit matters and audit engagement partners’ names significantly reduce audit quality of listed non-financial firms in Nigeria. It was recommended amongst others that regulatory pronouncements should be reviewed to embed peculiarities in the corporate world so as to enhance the communication of audit findings while the two variables observed in this study should be appropriately managed by the regulatory authorities.